2018
DOI: 10.1111/cpr.12436
|View full text |Cite
|
Sign up to set email alerts
|

The transient receptor potential vanilloid‐3 regulates hypoxia‐mediated pulmonary artery smooth muscle cells proliferation via PI3K/AKT signaling pathway

Abstract: These findings suggest that TRPV3 is involved in hypoxia-induced pulmonary vascular remodeling and promotes proliferation of PASMCs and the effect is, at least in part, mediated via the PI3K/AKT pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…The PI3K/AKT signaling pathway is important in VSMC proliferation and migration (15,31). Previous studies have reported that PI3K/AKT activation is important in promoting the migration of cultured VSMCs; however, this effect is increased by AKT depletion (32,33). Another study also found that PI3K/AKT inhibition blocked serum-stimulated VSMC lamellipodia formation (15).…”
Section: Discussionmentioning
confidence: 92%
“…The PI3K/AKT signaling pathway is important in VSMC proliferation and migration (15,31). Previous studies have reported that PI3K/AKT activation is important in promoting the migration of cultured VSMCs; however, this effect is increased by AKT depletion (32,33). Another study also found that PI3K/AKT inhibition blocked serum-stimulated VSMC lamellipodia formation (15).…”
Section: Discussionmentioning
confidence: 92%
“…It participates in the proliferation of vascular smooth muscle cells ,[ ] the generation of inflammatory factors such as VCAM‐1, and the autophagy of macrophages . In rats with hypoxic pulmonary hypertension, PI3K/Akt is activated, and the associated with protein level increases . LY294002 serves as an inhibitor of PI3K pathways, which can compete with PI3K in ATP binding sites and specifically inhibit PI3K activation.…”
Section: Discussionmentioning
confidence: 99%
“…Aijima et al argued that knockdown of TRPV3 suppressed proliferation of oral epithelia in mice [14]. Zhang et al revealed that TRPV3 promotes hypoxia-mediated pulmonary artery smooth muscle cells proliferation via increased [Ca 2+ ]i [15].Here, we investigated if TRPV3 plays a role in endothelial cell (EC) proliferation and tumor angiogenesis.…”
Section: Introductionmentioning
confidence: 92%